A decellularized human corneal scaffold for anterior corneal surface reconstruction - Polisetti, Naresh; Schmid, Anke; Schlötzer-Schrehardt, Ursula; Maier, Philip; Lang, Stefan J.; Steinberg, Thorsten; Schlunck, Günther; Reinhard, Thomas (Scientific Reports, 2021)
Allogenic transplants of the cornea are prone to rejection, especially in repetitive transplantation and in scarred or highly vascularized recipient sites. Patients with these ailments would particularly benefit from the possibility to use non-immunogenic decellularized tissue scaffolds for transplantation, which may be repopulated by host cells in situ or in vitro. So, the aim of this study was to develop a fast and efficient decellularization method for creating a human corneal extracellular matrix scaffold suitable for repopulation with human cells from the corneal limbus. To decellularize human donor corneas, sodium deoxycholate, deoxyribonuclease I, and dextran were assessed to remove cells and nuclei and to control tissue swelling, respectively. We evaluated the decellularization effects on the ultrastructure, optical, mechanical, and biological properties of the human cornea. Scaffold recellularization was studied using primary human limbal epithelial cells, stromal cells, and melanocytes in vitro and a lamellar transplantation approach ex vivo. Our data strongly suggest that this approach allowed the effective removal of cellular and nuclear material in a very short period of time while preserving extracellular matrix proteins, glycosaminoglycans, tissue structure, and optical transmission properties. In vitro recellularization demonstrated good biocompatibility of the decellularized human cornea and ex vivo transplantation revealed complete epithelialization and stromal repopulation from the host tissue. Thus, the generated decellularized human corneal scaffold could be a promising biological material for anterior corneal reconstruction in the treatment of corneal defects.
CRIS-Team Scopus Importer:2021-02-19